Inhibition Strength of Rosella (Hibiscus sabdariffa L.) Boiled Water on Salmonella typhi in vitro - Ayu Sutiany; Ratih Dewi Dwiyanti; Neni Oktiyani (Baiman Bauntung Batuah Center, 2019)
Rosella (Hibiscus sabdariffa L.) is a plant that can use as herbal medicine. Roselle calyx contains active compounds flavonoids, saponins, and tannins. These compounds can use as an antibacterial against Salmonella typhi. This study aims to determine the Minimum Inhibitory Concentration and Minimum Bactericidal Concentration and the effect of rosella cooking water concentration on Salmonella typhi in vitro. Experimental research with posttest only controls group design through dilution method. The results of the Minimum Inhibitory Concentration (MIC) study showed clarity at concentrations of 60%, 70%, 80%, 90%, and 100%. Minimum Bactericidal Concentration (MBC) results obtained the number of colonies at a concentration of 60% by one colony, at a level of 70%, 80%, 90%, and 100% showed no colony growth. Based on the results of the study concluded that there was an influence of rosella cooking water concentration on the growth of Salmonella typhi in vitro.